The Impact of A Successful Pterygium Excision on Corneal Astigmatism and Topography - Yousaf, Waseem; Humayun, Fakhar; Mumtaz, Sadaf; Taimoor, Ijlal; Ghani, Muhammad Usman; Khan, Taimoor Ashraf (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the impact of successful excision of pterygium on corneal astigmatism and topography.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Feb 2021 to Jul 2021.Methodology: All 52 patients of pterygium who underwent surgical excision of the pterygium during the study period were included. The size of pterygium was measured in millimeters. Pre-operative automated keratometry and corneal topography was done, and changes in astigmatism, surface asymmetry index, surface regularity index, uncorrected visual acuity and best corrected visual acuity were measured postoperatively on the 7th day. Paired sample t-test was applied between pre- and post-operative astigmatism, surface asymmetry index, surface regularity index, uncorrected visual acuity and best corrected visual acuity.Results: The mean age of participants was 42.02±13.3 years, with 22(42.3%) females and 30(57.7%) males. The male to female ratio is 1.36:1. The highest frequency of cases was noted in the age group, 31-50 years (42%), followed by 18-20 years (21%). Pterygium size was 2.25 to 4.10 mm, with a mean of 3.16±0.54mm. Pain and photophobia were noted in 5 cases. Pre- and postoperative comparison of astigmatism and corneal topography revealed a significant reduction in Surface Asymmetry Index and Surface Regularity Index values (p-value